Complete interruption of aortic arch, without persistent ductus arteriosus, in an adult. Issue 2 (February 1975) - Sharratt, G P; Carson, P; Sanderson, J M
Abstract : A case of complete interruption of the aortic arch in an adult is presented and the previous 8 reported cases are reviewed. Obliteration of the ductus is a feature of these cases, in contrast to the more common variety found in early childhood. Comments are made on the clinical distinction between the adult type of complete interruption of the aortic arch and coarctation of the aorta.